A novel Botrytis species is associated with a newly emergent foliar disease in cultivated Hemerocallis. - Robert T Grant-Downton (Public Library of Science (PLoS), 2014)
Foliar tissue samples of cultivated daylilies (Hemerocallis hybrids) showing the symptoms of a newly emergent foliar disease known as 'spring sickness' were investigated for associated fungi. The cause(s) of this disease remain obscure. We isolated repeatedly a fungal species which proved to be member of the genus Botrytis, based on immunological tests. DNA sequence analysis of these isolates, using several different phyogenetically informative genes, indicated that they represent a new Botrytis species, most closely related to B. elliptica (lily blight, fire blight) which is a major pathogen of cultivated Lilium. The distinction of the isolates was confirmed by morphological analysis of asexual sporulating cultures. Pathogenicity tests on Hemerocallis tissues in vitro demonstrated that this new species was able to induce lesions and rapid tissue necrosis. Based on this data, we infer that this new species, described here as B. deweyae, is likely to be an important contributor to the development of 'spring sickness' symptoms. Pathogenesis may be promoted by developmental and environmental factors that favour assault by this necrotrophic pathogen. The emergence of this disease is suggested to have been triggered by breeding-related changes in cultivated hybrids, particularly the erosion of genetic diversity. Our investigation confirms that emergent plant diseases are important and deserve close monitoring, especially in intensively in-bred plants.